Towards life cycle sustainability assessent of cities. A review of background knowledge (2017)
This article analyses whether existing LCA and sustainability methods can be used in the assessment of a city or an urban region. The approach is performed through the review of current existing LCA-based and sustainability standards and guidelines. A focus is put into those LCA-based standards specially designed for the built environment. Moreover, a review of non-LCA based standards, indices and guides for the assessment of the sustainability of countries, cities or urban regions is done. The purpose is to check if these assessment tools can provide good results in the absence of LCA-based assessments for cities and urban regions. This review demonstrates the lack of consensus in the definition of both, the city and its boundaries, which hinders the development of useful sustainability standards. Furthermore, it is concluded that current sustainability assessment tools miss, at least, one of these aspects: (i) holistic point of view, (ii) focus on various environmental impacts, (iii) a Life Cycle (LC) perspective, and (iv) the possibility to compare the results among different cities or urban regions. From the LCA perspective, the deficiencies found also include the need for a definition of the function, functional unit (FU), and reference flow (RF) of neighbourhoods, cities, and urban regions. © 2017 Elsevier B.V.